PENGARUH EARNING PER SHARE (EPS), RETURN ON EQUITY (ROE) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2014-2018 - Arum Narwita Sari; Sri Hermuningsih (Derivatif : Jurnal Manajemen, 2020)
This study aims to examine the effect of Earning per Share (EPS), Return on Equity Ratio (ROE) and Debt to Equity Ratio (DER) on stock returns with dividend policy as an intervening variable in consumer goods industry companies listed on the Indonesia Stock Exchange for the period 2014-2018. Data used is the panel data with the detail of 5 years time series and 20 companies of cross section data. The data obtained further processed by using the data analysis techniques is multiple linear regression supported by classical assumption test, namely the test of normality, multikoliniearity test, heteroskdastisity test and autocorrelation test. In this study also used Sobel test. Based on the results of data analysis shows that: (1) EPS has a positive and significant influence on the DPR which is indicated by 0.002 value and 0.000 for probability. (2) The ROE has a negative and insignificant influence on the DPR which is indicated by the -0.009 and probability of 0781. (3) DER has a positive and significant influence on the DPR which is indicated by the value of 3.087 and the probability of 0.030. (4) The DPR has insignificant negative influence on the stock return this is demonstrated by value -0.004 and probability of 0.377. (5) EPS has an insignificant negative influence on the stock return which is demonstrated by values 1.931 E-6 and probability 0.867. (6) ROE has a negative influence on the stock return which is demonstrated by values 8.957 E-7 and probability 0.999. (7) DER has an insignificant positive influence on the stock return which is demonstrated by the value of 0.046 and the probability of 0.244 and (8) DPR does not mediate the EPS, ROE and DER variables on stock return, this is indicated by the calculated z value is smaller than the z table value (-5 <1.96), (0.1270 <1.96) and (-6.7234 < 1.96). Dividend Policy (DPR) is not able to be an intervening variable of the EPS, ROE and DER variables on Saham Returns in the Consumer Goods Industry sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. This is proven bythe research of the Sobel test.Keywords: Earning per Share, Return on Equity, Debt to Equity Ratio, Dividend Policy, Stock Return